Features of using CRM systen in marketing and logistics management of service establishments - Serhii Voitovych; Nadia Bukalo; Igor Zhukov (Економічний форум)
The main purpose of the research in this scientific article is to substantiate the features of using CRM systems in marketing and logistics management in order to automate the processes of service and interaction with consumers of the service institution in the context of digitalization of marketing. The study of the practical principles of using CRM systems in marketing and logistics management of service institutions in the context of solving this problem indicated that CRM systems allow automating the processes of service and interaction of the institution with service consumers. However, the use of such CRM systems in relation to service institutions that provide different types of services has certain features both regarding the functioning of the institution and service processes, and the functional construction of the CRM system itself. The relevance of solving the proposed scientific problem is determined by the need to take into account the specifics of using CRM systems in marketing and logistics management of service institutions in order to ensure the effectiveness of such automation systems. This study was carried out taking into account the peculiarities of using CRM systems in marketing and logistics management of institutions: sanatorium-resort, medical, hotel and tourist, Physical culture and sports, consumer services and B2B. The methodological basis of this research is: logical-structural and system approaches, methods of management and marketing analysis, methods of logical generalization, analysis and synthesis, comparison, etc. The object of this research was the processes of using CRM-systems in marketing and logistics management of service institutions, and the subject – the features of implementing CRM-systems for automating the functions of interaction between the institution and consumers of services for sanatorium-resort, medical, hotel and tourist, physical culture, sports and consumer services, the basis for ensuring the effectiveness of using such CRM-systems. The article considers the features of using CRM-systems in marketing and logistics management of service institutions, functional components of CRM-systems, features of customer service processes in various service institutions and automation of relationships with consumers. This study theoretically justifies and confirms the conclusions, however, that the use of CRM systems should be carried out in the marketing and logistics management of service institutions, taking into account the specifics of the functioning of the institutions themselves (depending on the types of basic services or services that are provided), the specifics of the service processes in them, and the specifics and characteristics of CRM systems for automating the functions of interaction between the institution and service consumers. The results of the study can be used by marketers and managers of health resort, medical, hotel and tourist institutions, physical culture and sports and consumer services to improve the efficiency of using such CRM systems